Lipopolysaccharides detection on a grating-coupled surface plasmon resonance smartphone biosensor - Zhang, Jinling (2020)
We report a smartphone label-free biosensor platform based on grating-coupled surface plasmon resonance (GC-SPR). The sensor system relies on the smartphone's built-in flash light source and camera, a disposable sensor chip with Au diffraction grating and a compact disk (CD) as the spectra dispersive unit. The Au grating sensor chip was modified with a synthetic peptide receptor and employed on the GC-SPR detection of lipopolysaccharides (known as endotoxins) with detection limit of 32.5ng/mL in water. Upon incubation of various small and macro-molecules with the synthetic peptide modified sensor chips, we concluded the good selectivity of the sensor for LPS detection. In addition, the sensor shows feasibility for the detection of LPS in commonly used clinical injectable fluids, such as clinical-grade 0.9% sodium chloride intravenous infusion, compound sodium lactate intravenous infusion and insulin aspart. The developed sensor platform offers the advantage of portability and simplicity, which is attractive for point-of-care and remote detection of biomedical and environmental targets.